The Role of Maternal Smoking in Sudden Fetal and Infant Death Pathogenesis - Bednarczuk, Nadja; Milner, Anthony; Greenough, Anne (Frontiers in Neurology, 2020)
Maternal smoking is a risk factor for both sudden infant death syndrome (SIDS) and sudden intrauterine unexplained death syndrome (SIUDS). Both SIDS and SIUDS are more frequently observed in infants of smoking mothers. The global prevalence of smoking during pregnancy is 1.7% and up to 8.1% of women in Europe smoke during pregnancy and worldwide 250 million women smoke during pregnancy. Infants born to mothers who smoke have an abnormal response to hypoxia and hypercarbia and they also have reduced arousal responses. The harmful effects of tobacco smoke are mainly mediated by release of carbon monoxide and nicotine. Nicotine can enter the fetal circulation and affect multiple developing organs including the lungs, adrenal glands and the brain. Abnormalities in brainstem nuclei crucial to respiratory control, the cerebral cortex and the autonomic nervous system have been demonstrated. In addition, hypodevelopment of the intermediolateral nucleus in the spinal cord has been reported. It initiates episodic respiratory movements that facilitate lung development. Furthermore, abnormal maturation and transmitter levels in the carotid bodies have been described which would make infants more vulnerable to hypoxic challenges. Unfortunately, smoking cessation programs do not appear to have significantly reduced the number of pregnant women who smoke.